Legal bases of material support of militia workers of the Ukrainian SSR in the 20s of the XX century - S. V. Vasyliev (Bulletin of Kharkiv National University of Internal Affairs)
The scientific study is devoted to the peculiarities of the legal regulation of the militia workers' material support of the Ukrainian SSR in the 20s of the twentieth century. The objectives of the scientific work are to establish a list of legal acts that regulated the conditions for the militia workers' social security and to analyze their norms. It is necessary to determine the specifics of fulfilling the requirements of the legislation on the material support of militia officers. The scientific novelty of the study lies in the fact that a significant number of archival documents have been used in scientific circulation for the first time.